Hubungan Kadar Kolesterol dengan Hipertensi - Sinaga, Elizabeth Mega; Musyabiq, Sofyan (Medula, 2024)
Hypertension is one of the diseases that become a problem in the world because it increases the risk of cardiovascular disease, brain, kidneys, and others. However, this is often not realized because it is often without symptoms. Lifestyle plays a role in the regulation of blood pressure and contributes to the development of hypertension. One of the causes of hypertension is cholesterol. The buildup of cholesterol in the blood will clog blood vessels and stiffness occurs so that blood pressure increases. This study aims to determine the relationship between cholesterol levels and hypertension. This research method was carried out by meta-analysis research through searching articles on Google Scholar with the formula, 'The Relationship of Cholesterol Levels with Hypertension' with a range of 2019-2024. From 8 literature reviews, it was found that the majority of respondents studied who experienced elevated cholesterol levels would also experience an increase in blood pressure. After this study, there was a relationship between cholesterol levels and hypertension.